Cholinergic Enhancement Increases the Effects of Voluntary Attention but Does Not Affect Involuntary Attention - Rokem, Ariel (Nature Publishing Group, 2010)
Voluntary visual spatial attention can be allocated in a goal-oriented manner to locations containing behaviorally relevant information. In contrast, involuntary attention is automatically captured by salient events. Allocation of attention is known to be modulated by release of the neurotransmitter acetylcholine (ACh) in cerebral cortex. We used an anti-predictive spatial cueing task to assess the effects of pharmacological enhancement of cholinergic transmission on behavioral measures of voluntary and involuntary attention in healthy human participants. Each trial began with the presentation of a cue in a peripheral location. In 80% of the trials, a target then appeared in a location opposite the cue. In the remaining 20% of trials, the target appeared in the cue location. For trials with short stimulus onset asynchrony (SOA) between cue and target, involuntary capture of attention resulted in shorter reaction times (RTs) to targets presented at the cue location. For long SOA trials, allocation of voluntary attention resulted in the opposite pattern: RTs were shorter when the target appeared in the expected (opposite) location. Each subject participated in two sessions: one in which the cholinesterase inhibitor donepezil was administered to increase synaptic ACh levels and one in which placebo was administered. Donepezil selectively improved performance (reduced RT) for long SOA trials in which targets appeared in the expected location. Thus, cholinergic enhancement augments the benefits of voluntary attention but does not affect involuntary attention, suggesting that they rely on different neurochemical mechanisms.